Effect of Hydrogen-Ion Concentration on the Growth and Reproduction of Curvularia eragrostidis (Henn.) J. A. Mey. - Prajapati, V. P.; Gajre, N. K.; Tandel, D. H.; Deshmukh, A. J.; Bambharolia, R. P. (International Journal of Economic Plants, 2016)
Fungi are very sensitive to their growth as well as sporulation are greatly influenced by pH of the substrate. Studies on eight different pH regimes revealed that the fungus Curvularia eragrostidis causing leaf tip blight of spider lilly produced maximum dry mycelial weight with good sporulation in pH ranging from 4.0 to 6.5.